Hubungan Cost Estimation Reliability, Sales Volume Forecasting, Dan Cost Structure Flexibility Terhadap Keberhasilan Cost-Volume-Profit Analysis Sebagai Alat Perencanaan: The Relationship of Cost Estimation Reliability, Sales Volume Forecasting, and Cost Structure Flexibility to the Success of Cost-Volume-Profit Analysis as a Planning Tool - Rafi, Moch Irsyad Ainur; Aprelianingrum, Ainiyah; Indraswari, Sagung Ayu Dwianjani Trisna; Erong, Elmiano Artanto Epot; Wicaksono, Fajar; Yega Putriani, Apryla Ayu; Hwihanus, Hwihanus; Yovita, Maria (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the effect of cost estimation reliability, sales volume forecasting, and cost structure flexibility on the effectiveness of Cost-Volume-Profit (CVP) analysis as a managerial planning tool. CVP analysis helps companies understand the relationship between costs, sales volume, and profit, and supports decision-making for operational planning. This research uses a descriptive approach with PT Mayora Indah Tbk as the object of study, a company characterized by complex cost structures and fluctuating market demand. The results indicate that accurate cost estimation, reliable sales forecasting, and flexible cost structures play an important role in improving the reliability of CVP analysis outcomes. The more accurate the estimations and forecasts, and the more adaptable the cost structure, the more effective CVP becomes in supporting profit planning and operational strategy. These findings highlight the importance of a systematic and adaptive estimation and forecasting system within a dynamic business environment.